Relations among the regional price index, market structures, and capital parameters of the region - Jiří Kraft (Trends Economics and Management, 2018)
Purpose of the article: This paper focuses attention on regional price indices (RPI) that reach across regions, respectively Czech regions, and different levels. Methodology/methods: The article mainly analyses the relation between the RPI and the particular form of market structures at the regional level, while also looking at the link between the RPI and capital parameters of each region. The methodology used is in the case of the first relation based on graphical models; in the second case selected statistical methods - correlation and regression analysis - were applied. Scientific aim: The aim of the article is to verify the existence of the link between the RPI and the market structures, but also the RPI and the capital parameters of the region. Findings: The results of correlation analysis confirm the assumption that RPI growth can also be observed in regions where the capital parameters are at a higher level, than in regions with lower values of capital parameters. On the contrary, the regression analysis points to low statistical importance of the dependence of the RPI on the capital assets of the region as demonstrated by the evaluation of 13 regions in Czech Republic (excluding Prague). However, for 14 regions this dependence is already statistically significant, but the figure for Prague is so distant from all of the others that it may be described as a typical case of so-called distant observation. Conclusions: A reliable and universally verifiable relation between the RPI and the particular form of the market structures most likely does not exist. For further research, it would be interesting to reverse the link between RPI and regional capital characteristics, and ask whether a low RPI can be a factor for a subsequent capital inflow.
Keywords: L11; R32; 650; regional price index; market structures; monopoly; oligopoly; monopolistic competition; regional capital parameters